2009
DOI: 10.1016/j.atherosclerosis.2008.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of reactive oxygen species attenuates aneurysm formation in a murine model

Abstract: Reactive oxygen species (ROS) are increased in human abdominal aortic aneurysms (AAA). NADPH oxidases are the predominant source of superoxide anion (O 2 − ) in the vasculature. Inducible nitric oxide synthase (iNOS) produces significant amount of nitric oxide (NO) during inflammatory processes. We hypothesized that ROS produced by NADPH oxidases and iNOS play an important role in aneurysm formation. We examined this hypothesis using selective blockade of NADPH oxidases and iNOS in a murine model of AAA. Mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 28 publications
(33 reference statements)
4
101
1
Order By: Relevance
“…13 It has been reported that ROS generation is markedly upregulated in the aortic aneurysmal tissues, whereas inhibition of ROS production attenuates AAA formation. 3,23 In this study, Tregs treatment substantially reduced the production of ROS in the aortic aneurysmal tissues in ApoE −/− mice, suggesting that blunted oxidative stress may be an important mechanism in preventing AAA formation in our mouse model. NF-κB is a key proinflammatory transcription factor responsible for the regulation of the cytokine network in vascular SMCs.…”
Section: Discussionmentioning
confidence: 53%
“…13 It has been reported that ROS generation is markedly upregulated in the aortic aneurysmal tissues, whereas inhibition of ROS production attenuates AAA formation. 3,23 In this study, Tregs treatment substantially reduced the production of ROS in the aortic aneurysmal tissues in ApoE −/− mice, suggesting that blunted oxidative stress may be an important mechanism in preventing AAA formation in our mouse model. NF-κB is a key proinflammatory transcription factor responsible for the regulation of the cytokine network in vascular SMCs.…”
Section: Discussionmentioning
confidence: 53%
“…It is therefore surprising that the 16p13.1 duplications implicated in aortic disease may result in increased contractility. Both contraction and increased metabolic stress could lead to increased ATP turnover in SM1 cells, potentially driving increased production of reactive oxygen species, which have been previously associated with aortic disease (58,59). Alternatively, vascular SMCs typically retain a large reserve of unphosphorylated myosin light chain to respond rapidly to changes in biomechanical forces.…”
Section: Discussionmentioning
confidence: 99%
“…35 The infusion of Ang II for 28 days increased aortic ROSs, as indicated by enhanced oxidized DHE fluorescence intensity in AAA ( Figure 5, A and B), and cardiac NADPH oxidase activity and increased plasma levels of 8-isoprostane, another index of oxidative stress, 36 in Apoe À/À /Cyp1b1 þ/þ mice, which was inhibited by treatment with TMS or by Cyp1b1 gene disruption ( Figure 5, C and D). Ang II increases COX-2 expression in VSMCs via p38 mitogen-activated protein kinase, 37 and this pathway been implicated in the pathogenesis of AAA.…”
Section: Tms or Cyp1b1 Gene Disruption Minimizes Increases In Aorticmentioning
confidence: 98%
“…Treatment with TMS or Cyp1b1 Gene Disruption Minimizes MMP Expression and ECM Degradation in Ang IIeInduced AAA in Apoe À/À /Cyp1b1 þ/þ Mice Aneurysm lesions are characterized by degradation of the ECM components by proteolytic enzymes like MMP-2 and -9 35 ; therefore, we assessed the contribution of CYP1B1 in the expression of MMP and ECM components (collagen, elastin, and a smooth muscle actin) in AAA due to Ang II infusion for 28 days. Increased fluorescence intensity of MMP-2 and -9 staining was observed in the aorta sections from Apoe À/À /Cyp1b1 þ/þ mice infused with Ang II but not in mice concurrently treated with TMS or in Apoe À/À / Cyp1b1 À/À mice ( Figure 4, A and B).…”
Section: Role Of Cyp1b1 In Aortic Aneurysmsmentioning
confidence: 99%